The Effect of Liquid Organic Fertilizer (LOF) from Rotten Fruit on the Growth of Chili Pepper Plants (Capsicum frutescens L.) - Nafi'ah, Zidna Ilma; Sedijani, Prapti; Japa, Lalu (Jurnal Biologi Tropis, 2025)
Fruit trash is a waste product that is typically dumped in the open without any additional handling, which can lead to illness, contamination of the air and water, and other issues. This study aims to analyze the effect and determine the right dose of using liquid organic fertilizer from rotten fruit on the growth of plant of cayenne pepper (Capsicum frutescens L.). This study was an experimental with a randomized design (CRD). There were 5 treatments, namely P0 (control/using 1000 mL water), P3 (300 mL LOF + 700 mL water or 30% concentration), P6 (600 mL LOF + 400 mL water or 60% concentration), P9: 900 mL LOF + 100 mL water or 90% concentration, and P12 (1200 mL liquid organic fertilizer or 100% concentration). Vegetative development (stem height, leaf area, and number of leaves) and generative growth (fruit fresh weight) were among the measurement criteria. The statistical test (ANOVA) was used to analyze the data at a significance level of 0.05. The outcome shown that the growth of cayenne pepper was considerably impacted by the usage of rotting fruit LOF. Following additional testing using the least significant difference test (LSD), the study's findings indicated that 60% (P6) of rotten fruit LOF was the ideal dosage for cayenne pepper's vegetative and generative growth, with an average plant stem height of 35.10 cm, leaf area of 53.90 cm2, number of leaves of 37 strands, and fresh fruit weight of 55.35 grams.